A Mixed-Methods Quick Strike Research Protocol to Learn About Children With Complex Health Conditions and Their Families. Issue 1 (20th September 2017) - Doucet, Shelley; Nagel, Daniel A.; Azar, Rima; Montelpare, William J.; Charlton, Pat; Hyndman, Nicky; Luke, Alison; Stoddard, Roger
Advances have been made to improve health care for children with complex health conditions (CCHCs); however, little is known of the needs of these children and their families in the Canadian context. In this article, we describe our Canadian Institutes of Health Research funded Quick Strike protocol, a mixed-methods multisite research project that explored CCHC and their families in two Canadian provinces. The aims were (a) to describe and define CCHC, (b) to understand the needs of CCHC and their families, (c) to identify gaps and barriers to services for this population, and (d) to adapt and test the application of a computerized algorithm to yield information on CCHC. The mixed-methods design was comprised of four components: three qualitative and one quantitative. We describe the components of this project and outline the methods and procedures of data collection and analysis for each component. One of the main sources of data was interviews from 121 stakeholders, which included CCHC and family members, as well as health, social, and education professionals. This Quick Strike project was designed to engage stakeholders and the public with integrated knowledge translation threaded as a core element throughout the research process. Multiple strategies were used to validate and disseminate early findings from the research. As we outline in this article, this research project provided the foundation for one innovative service model of care, NaviCare/SoinsNavi, and spawned a number of additional outcomes such as a secondary analysis of the data to describe interprofessional collaboration for CCHC.